10 Years after the Crisis: Thailand's Financial System Reform - Lukas Menkhoff; Chodechai Suwanaporn (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper uses the framework of long-term financial system development to describe and assess the reform process in Thailand after 1997. The present financial reforms are well in line with the pattern of financial development found in the academic literature. A detailed analysis of capital markets, specialized financial institutions and supervisory regulation shows recent advancements and open issues. The rapid rise of non-banks financial institutions can serve as a paradigmatic example of market driven dynamism requiring appropriate policy action. Overall, the building of modern and sophisticated financial institutions is an ongoing process which should consider human resource constraints.
Keywords: G2; O1; 330; Financial institutions; financial development; Thailand